Analysis of Determinants of Female Labor Force Participation Rate in East Java Province 2020-2023 - Yumna Lathufinisa, Rajisya; Ashar, Khusnul (Journal of Development Economic and Social Studies, 2025)
This study examines the influence of education, the number of people taking care of households, economic growth, and district and city minimum wages on the female labor force participation rate (TPAK) in 38 regencies/cities in East Java Province. Through data obtained from the Central Statistics Agency, it shows a gap in participation between the male and female workforce. The average female labor force participation rate is at 50% while the male is at 80%. This study uses a quantitative approach through the panel data regression method from 38 regencies/cities in East Java Province in 2020-2023. The results of the study show that the average length of schooling for women has a positive and insignificant effect on the female labor force participation rate (TPAK) in 38 regencies/cities in East Java Province. The number of people taking care of households has a negative and significant effect on female TPAK in East Java Province. Economic growth has a negative and insignificant effect on female TPAK in East Java Province. The UMK has a positive and significant effect on female TPAK in East Java Province.